Chromosome-scale assembly and analysis of yellow Camellia (Camellia limonia) genome reveal plant adaptation mechanism and flavonoid biosynthesis in karst region - Yingying Lu; Huimin Liang; Jialin Liao; Xianglong Li; Yinxia Rong; Ruyin Mo; Jianmin Tang; Maoteng Li; Xiangdong Kong; Yang Huang; Yu Liang (Global Ecology and Conservation)
Yellow Camellia is an endangered and protected wild plant with unique medicinal value. Among the Camellia Sect. Chrysantha Chang, certain species (e.g. Camellia limonia) can grow in karst regions. The karst region is a highly sensitive ecosystem with low environmental capacity. However, the molecular mechanisms underlying the adaptation of yellow camellia to karst regions remain unclear. Here, we present a high-quality genome with 15 chromosome groups with an N50 of 198.92 Mb. The divergence between C. limonia and Camellia sinensis occurred approximately 6 million years ago, indicating that the Himalayan uplift event may led to species differentiation. This enables C. limonia to thrive in a unique ecological environment like the karst region. Flavonoid compounds play a significant role in the interaction between plants and their environment. In comparison to Theaceae family genomes, C. limonia exhibits an increased number of gene family members involved in the flavonoid biosynthesis pathway, including UDP-glycosyltransferases and chalcone reductase. Additionally, two gene clusters associated with flavonoid biosynthesis were identified in the genome of C. limonia. Furthermore, comparative genomics analysis revealed the expansion of genes associated with karst environment adaptation in the genome of C. limonia, such as calmodulin genes and genes related to Calcium ion transmembrane transport. Additionally, at the gene expression level, it was observed that the secondary metabolism-related genes may be involved in the calcium tolerance of C. limonia. These findings provide important insights into the evolution of C. limonia, offering references for the study of plants in karst areas.